2021
DOI: 10.1186/s12935-021-02381-1
|View full text |Cite
|
Sign up to set email alerts
|

M2 macrophages secrete CXCL13 to promote renal cell carcinoma migration, invasion, and EMT

Abstract: Objective M2 macrophages are associated with a poor prognosis in a variety of malignancies. There are, however, few relevant investigations in clear cell renal cell carcinoma (ccRCC). Methods The expression of M2 macrophages in ccRCC tissues was first discovered using immunohistochemistry in this study. Then, M2 macrophages were created in vitro to see how they affected the proliferation, migration, invasion, and EMT of ccRCC cells. Using qPCR and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…M2 macrophages, CD8 + T cells, and fibroblasts were more abundant in the high-risk group than in the low-risk group. These immune cells were associated with the poor prognosis of patients with KIRC ( Davidsson et al, 2020 ; Komohara et al, 2011 ; Li et al, 2020 ; Nakayama et al, 2018 ; Xie et al, 2021 ; You et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M2 macrophages, CD8 + T cells, and fibroblasts were more abundant in the high-risk group than in the low-risk group. These immune cells were associated with the poor prognosis of patients with KIRC ( Davidsson et al, 2020 ; Komohara et al, 2011 ; Li et al, 2020 ; Nakayama et al, 2018 ; Xie et al, 2021 ; You et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the molecular regulatory mechanisms of different subtypes has become a research hotspot in the field of cancer. m6A is the most common RNA methylation modification, and the molecular subtype based on m6A regulators can well-predict the efficacy of immunotherapy and evaluate the prognosis of patients (Shen et al, 2020;Zhong et al, 2021). 5mC, another type of methylation modification, can also wellpredict the prognosis of patients (Hu Y et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages create an environment conducive to tumor survival by releasing growth factors, chemokines, and other inflammatory mediators ( Solinas et al, 2009 ; Lin et al, 2019 ). In addition, M2 macrophages can also promote tumor metastasis and invasion by promoting angiogenesis and other pathways ( Jetten et al, 2014 ; Xie et al, 2021 ). To further analyze the differences in composition and function within M2 macrophages, we used bioinformatics to perform an in-depth analysis at the single cell level.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that CCL2 and CCL5 could promote M2 macrophages generation in TME ( Smida et al, 2020 ; Kang et al, 2021 ). M2 macrophages secreted chemokines such as CCL17 and CXCL13 ( Liu Y. et al, 2020 ; Xie et al, 2021 ). Meanwhile, CCL19 and CCL21 were shown to be associated with M1 macrophage chemotaxis ( Xuan et al, 2015 ; Boibessot et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%